Too big to fail? The US debt crisis & its implications - Ng, Sophie. (2012)
The US has managed to pull back from the brink of bankruptcy, saved by a last-ditch effort to raise the debt ceiling. The danger is not over as the shadow of a possible downgraded credit rating, and further indebtedness, threaten to affect global stability.